Thermometric absorption spectroscopy through active locking of microbubble resonators - Frigenti, Gabriele; Farnesi, Daniele; Vesco, Guglielmo; Centi, Sonia; Ratto, Fulvio; Pelli, Stefano; Murzina, Tatyana V.; Nunzi Conti, Gualtiero; Soria, Silvia (Frontiers in Physics, 2023)
We implemented a Microbubble Resonator (MBRs) as an opto-thermal transducer to reconstruct the absorption spectrum of a nanoparticle suspension through its temperature increase. The experimental configuration features the MBR as both the vial containing the suspension and the optical transducer, allowing for a sensitive ultra-compact system with a straightforward microfluidic integration. With respect to a previous publication, the active lock of the MBR resonance produced an order-of-magnitude improvement in the system performance and a smooth absorption reconstruction. Additionally, since the detection process is temperature-based, the measurement is intrinsically insensitive towards scattering spectrum, both of the particles and of the host liquid. These features make the MBR system an interesting candidate for the characterisation of extremely small samples in the context of medical diagnosis from whole biological samples, quality controls for food safety or chemical production processes, and, in general, for the measurement of absorption in opaque mediums.